Responses of ASEAN-5 to China stock market reforms - Hooy, Chee Wooi; Goh, Kim Leng; Cheong, Kee Cheok (Institute of China Studies, 2018)
China’s influence on the financial sector of ASEAN has been more significant as a result of the recent strengthening of China’s monetary and exchange rate policies, its growing financial sector, as well as the fast expansion of its corporate and financial investment around the world. This paper analyses the influence of the China stock market on its ASEAN counterparts over the period of 2002-2015. The extent of ASEAN stock market responses to three major stock market trading reforms in China are examined. These reforms include the liberalization of the A-shares to Qualified Foreign Institutional Investors (QFII reform) starting from 5th November 2002, the split share structure reform starting from 29th April 2005, and the lifting of short sale constraints and margin-trading starting from 21st March 2010. Data on 2,166 public listed firms in Indonesia, Malaysia, the Philippines, Singapore and Thailand are used to investigate if their responses, normalized to the responses of listed firms in China, are economically significant and have amplified over time with the increased influence of China’s economy in the global market. Evidence shows that firms from Indonesia, Malaysia and Singapore have significant and increased relative responses to these reforms in the China market. The increase is particularly drastic in response to the short-sale reform in 2010. Listed firms from the Philippines and Thailand did not exhibit similar responses. The result is consistent with the development of bilateral trade ties between China and these ASEAN countries.